A new testing and training device for hamstring muscle function - Giacomo, J.-P.; Lahti, J.; Hegyi, A.; Gerus, P.; Morin, J.-B. (Sport Performance & Science Reports, 2018)
Hamstring injury is a major, unresolved, health issue in sports (1), with two main injury mechanisms: sprint-related and overstretching-related strains (2-4). This raises the question of e ective prevention and rehabilitation protocols (5,6), during which hamstring strength output, especially during lengthening actions, is a central component (9,10). The aim of this technical report is to introduce a novel device for potentially further optimizing hamstrings strength training and testing.